The Question is:

Show that

9 + 11 = 28 simplifies to 9x ²+ 29 x - 28 = 0

x+2 x ( x+2)

Posted Sat 21st May, 2011 @ 12:29 by

Miranda
heres what you do:

1. MAKE IT =0

9+(11/x+2) -28/[x(x+2)] = 0

2. multiply by the brackets

9(x+2)(x) +11(x) -28 = 0

3. expand the brackets

9x^2 +18x +11x - 28 =0

4. simplify

9x^2 +29x-28=o

BAMMMM

Answered Sat 21st May, 2011 @ 12:42 by

Georgina
could you rewrite it because im sure 9+11 doesnt =28 **

Answered Sat 21st May, 2011 @ 12:31 by

Georgina
Its an algebraic question and it's impossible to type it as a fraction on here but it should be

9 + 11 28

_____ ( over) _________

x + 2 x ( x + 2)

Answered Sat 21st May, 2011 @ 12:37 by

Miranda
Ohh and show that it simplifies to 9 x ( sqaured) + 29 x -28 = 0 :) x

Answered Sat 21st May, 2011 @ 12:38 by

Miranda
Ahh thank you very much!! Really helped ! :)

Answered Sat 21st May, 2011 @ 12:47 by

Miranda
its alright x

ive got some maths resources on that sorta stuff x

Answered Sat 21st May, 2011 @ 12:53 by

Georgina